Pengaruh Waḥdat Al-Wujūd dalam Pemikiran Islam di Nusantara - Kautsar Azhari Noer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
Among the great mystics in history, Ibn al-‘Arabi (560-683/1165-1240) stands out as one of the most influential. His mystical ideas, particularly the doctrine of Waḥdat al-Wujūd (Unity of Being), spread throughout the Islamic world and left a profound impact on Sufi philosophy. This paper explores the influence of Waḥdat al-Wujūd on Islamic thought in the Nusantara region. It examines the historical development of this doctrine, identifies key Sufi scholars who embraced and disseminated it, and analyzes the factors that facilitated or hindered its acceptance. Additionally, this study considers the future trajectory of Waḥdat al-Wujūd in Nusantara, assessing its relevance in contemporary Islamic discourse.